Alice Paul : claiming power - Zahniser, Jill Diane (Oxford University Press, 2014)
This biography of Alice Paul, long an elusive figure in the political history of American women, offers the first in-depth examination of the sources of Paul's ambition and the development of her political consciousness. Focusing on Paul's early years and suffrage leadership, the authors bring fresh insights to the persistent questions about Alice Paul and her legacy.